Intra-abdominal compartment syndrome: risk factors, complications and treatment - Almottowa, Hisham A.; Nasser, Mohammad E.; Altamimi, Mohammad G.; Alfodari, Fatma A.; Alsherbi, Raghad K.; Alherz, Sarah H.; Aldandan, Ali R.; Alshatti, Qanot N.; Alyousef, Reem M.; Alsaedi, Ghadi A.; Alhilali, Maysa F.; Alsharif, Hanouf S. (International Journal Of Community Medicine And Public Health, 2022)
An elevation in intra-abdominal pressure is the clinical condition referred as abdominal compartment syndrome (ACS). The prevalence varies depending on the patient characteristics considered, exponentially rising in life-threatening situations such as trauma, shock and burn patients. The syndrome can also occur after surgical operations like abdominal organ transplantation, post-transplant kidney syndrome among various others. All physiological systems, but particularly the cardiovascular, respiratory, renal, and neurological systems, are impacted by ACS. Blood flow to numerous organs is influenced by ACS and intra-abdominal hypertension. Recognizing and identifying ACS, its risk factors, and clinical symptoms can help to lower the associated morbidity and mortality. The purpose of this research is to review the available information about ACS: risk factors, complications and treatment. ACS is a fatal condition if not diagnosed and treated timely. Patients who have undergone extensive abdominal surgery, experienced septic issues, received intensive fluid replacement, sustained abdominal trauma are at an increased risk of developing ACS. Multiple-organ failure, prolonged recovery, acute kidney injury, low cardiac output, elevated cranial pressure and respiratory distress are the complications of ACS. ACS can occur regardless of the primary diagnosis or treating medical speciality. Surgical decompression, vascular volume replacement, prokinetic drugs, efficient curarization, and percutaneous drainage of large-volume ascites are the treatment strategies for ACS. Combining the underlying disease's therapy approach, patient stabilization, and ACS management is necessary to establish the best course of care. Early detection of ACS is essential for management and the treatment of the patients.